2009
DOI: 10.1007/s10620-009-0845-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Selective Granulocyte, Monocyte Adsorptive Apheresis with the Adacolumn® Device in Ulcerative Colitis

Abstract: The purpose of this meta-analysis was to determine whether selective adsorptive granulocyte and monocyte apheresis (GMA apheresis) using the Adacolumn device can effectively reduce clinical symptoms and endoscopic signs of inflammation in patients with ulcerative colitis (UC). A comprehensive search for randomized controlled trials (RCTs) published up to May 2008 was performed. Each study's quality was evaluated, and the data reported in the results were abstracted. Pooled relative risk (RR) estimates and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
2
37
0
3
Order By: Relevance
“…The same conclusion was drawn in a review from Habermalz and Sauerland [49]. More patients responded to GMA than to an increase in steroid dosage.…”
Section: Single Center Experiencesupporting
confidence: 72%
“…The same conclusion was drawn in a review from Habermalz and Sauerland [49]. More patients responded to GMA than to an increase in steroid dosage.…”
Section: Single Center Experiencesupporting
confidence: 72%
“…22 Furthermore, the incidence of side effects was approximately 80% lower with apheresis than steroids. Others have also shown that dosages of concomitant steroid can subsequently be tapered or discontinued following apheresis.…”
mentioning
confidence: 99%
“…GMA therapy has been reported as an effective therapy with minimal side effects for patients with UC, particularly in refractory cases to conventional drug therapy [8,14,16,17,18,19,20,21]. In contrast, a study in the United States reported no significant difference between the sham group and the GMA group [45].…”
Section: Discussionmentioning
confidence: 99%
“…GMA is also associated with marked increase in serum level of the anti-inflammatory cytokine, IL-10 [15]. Several studies have reported significant efficacy in patients with UC following a course of GMA [8,14,16,17,18,19,20,21]. It has been reported that the overall response (remission or significantly improvement) of GMA treatment increased from 58.5 to 77.7% [14,18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation